Notes on the figures of Pyrrho and Timon in Sextus Empiricus’ work - Fita, Tristán (Estudios de Filosofía, 2019)
This paper presents the main features that Sextus Empiricus draws from those he designates as his predecessors and, at the same time, explains how this reading influences his own skeptical ideal. Specifically, we will point out the main characteristics of the way that Pyrrho and Timon are portrayed in the Sextan writings. We consider that a study of these figures in the Sextan corpus will result in a better understanding of the philosopher’s own skeptical ideal. In this way, our main objective will be to show that Sextus uses different argumentative strategies to model much of his own skeptical stance. At the same time, we intend to claim Sextus as an authentic writer, since he has often been called a copyist without originality when he performs exegesis of this type on the aforementioned figures.